Energy and macronutrients intake of children attending kindergartens in Kosovo (full day program-8 hours) - Rysha, Agim; Gjergji, Tahire M; Ploeger, Angelika (Progress in Nutrition, 2022)
Abstract: Aim: Understanding preschool children’s food consumption in kindergartens may be one possibility to find out whether preschool children’s energy is adequate. The aim of the study was to evaluate the energy and macronutrient intake by children in kindergartens in Kosovo.Methods: Preschool children (n = 469) aged 1